Diagnosis of Smith-Lemli-Opitz syndrome by ultraviolet spectrophotometry - Scalco,F.B. (2003)
Smith-Lemli-Opitz syndrome (SLOS) is an autosomal recessive disorder due to an inborn error of cholesterol metabolism, characterized by congenital malformations, dysmorphism of multiple organs, mental retardation and delayed neuropsychomotor development resulting from cholesterol biosynthesis deficiency. A defect in 3ß-hydroxysteroid-delta7-reductase (delta7-sterol-reductase), responsible for the conversion of 7-dehydrocholesterol (7-DHC) to cholesterol, causes an increase in 7-DHC and frequently reduces plasma cholesterol levels. The clinical diagnosis of SLOS cannot always be conclusive because of the remarkable variability of clinical expression of the disorder. Thus, confirmation by the measurement of plasma 7-DHC levels is needed. In the present study, we used a simple, fast, and selective method based on ultraviolet spectrophotometry to measure 7-DHC in order to diagnose SLOS. 7-DHC was extracted serially from 200 µl plasma with ethanol and n-hexane and the absorbance at 234 and 282 nm was determined. The method was applied to negative control plasma samples from 23 normal individuals and from 6 cases of suspected SLOS. The method was adequate and reliable and 2 SLOS cases were diagnosed.